Preliminary CFD Assessment of an Experimental Test Facility Operating with Heavy Liquid Metals. (1st June 2017) - Lizzoli, Matteo; Borreani, Walter; Devia, Francesco; Lomonaco, Guglielmo; Tarantino, Mariano
Abstract : The CFD analysis of a Venturi nozzle operating in LBE (key component of the CIRCE facility, owned by ENEA) is presented in this paper. CIRCE is a facility developed to investigate in detail the fluid-dynamic behavior of ADS and/or LFR reactor plants. The initial CFD simulations have been developed hand in hand with the comparison with experimental data: the test results were used to confirm the reliability of the CFD model, which, in turn, was used to improve the interpretation of the experimental data. The Venturi nozzle is modeled with a 3D CFD code (STAR-CCM+). Later on, the CFD model has been used to assess the performance of the component in conditions different from the ones tested in CIRCE: the performance of the Venturi is presented, in terms of pressure drops, for various operating conditions. Finally, the CFD analysis has been focused on the evaluation of the effects of the injection of an inert gas in the flow of the liquid coolant on the performance of the Venturi nozzle.